2008
DOI: 10.1007/s12187-008-9020-8
|View full text |Cite
|
Sign up to set email alerts
|

Child Well-Being in Central and Eastern European Countries (CEE) and the Commonwealth of Independent States (CIS)

Abstract: This is the first attempt to produce a multidimensional index of the wellbeing of children in the CEE/CIS countries. It follows the methods employed in similar indices produced by the same authors for EU and OECD countries. Indicators are derived from existing survey and administrative sources, they are combined into components and the components are combined into seven domains of well-being. There is considerable variation in the performance of different countries in different domains. The domains are combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 12 publications
0
31
1
1
Order By: Relevance
“…What is perhaps surprising, in this and other studies (e.g. Richardson et al 2008), is that the highest levels of general satisfaction are found in Kyrgyzstan, the poorest country, and a much lower level of general satisfaction in Georgia compared with the other three countries. We return to this in the discussion below.…”
Section: General Satisfactioncontrasting
confidence: 48%
See 3 more Smart Citations
“…What is perhaps surprising, in this and other studies (e.g. Richardson et al 2008), is that the highest levels of general satisfaction are found in Kyrgyzstan, the poorest country, and a much lower level of general satisfaction in Georgia compared with the other three countries. We return to this in the discussion below.…”
Section: General Satisfactioncontrasting
confidence: 48%
“…Interestingly, on a normalised index of subjective well-being for young people for Surviving the Transformation 217 21 CEE and CIS countries Kyrgyzstan had the highest score, ?1 SD above the meanwhile Kazakhstan was just under -0.5 SD below the mean and Armenia -1.10 with Georgia having the mean score (Richardson et al 2008). We can only speculate as to why people are more satisfied in Kyrgyzstan than would be expected given its level of economic development.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The first was a comparison of child well-being in the European Union (EU) 25 countries (Bradshaw, Hoelscher and Richardson 2007). Richardson, Hoelscher and Bradshaw (2008) did a comparison of child well-being in the Central and Eastern European Countries and the Commonwealth of Independent States (CEE/CIS) countries. This was followed by a revision of the EU index this time covering 27 countries (Bradshaw and Richardson 2009).…”
Section: Introductionmentioning
confidence: 99%